Binge Alcohol Drinking Alters Synaptic Processing of Executive and Emotional Information in Core Nucleus Accumbens Medium Spiny Neurons - Kolpakova, Jenya; van der Vinne, Vincent; Giménez-Gómez, Pablo; Le, Timmy; You, In-Jee; Zhao-Shea, Rubing; Velazquez-Marrero, Cristina; Tapper, Andrew R.; Martin, Gilles E. (Frontiers in Cellular Neuroscience, 2021)
The nucleus accumbens (NAc) is a forebrain region mediating the positive-reinforcing properties of drugs of abuse, including alcohol. It receives glutamatergic projections from multiple forebrain and limbic regions such as the prefrontal cortex (PFCx) and basolateral amygdala (BLA), respectively. However, it is unknown how NAc medium spiny neurons (MSNs) integrate PFCx and BLA inputs, and how this integration is affected by alcohol exposure. Because progress has been hampered by the inability to independently stimulate different pathways, we developed a dual wavelength optogenetic approach to selectively and independently stimulate PFCx and BLA NAc inputs within the same brain slice. This novel approach functionally demonstrates that PFCx and BLA inputs synapse onto the same MSNs where they reciprocally inhibit each other presynaptically in a strict time-dependent manner. In alcohol-naïve mice, this temporal gating of BLA-inputs by PFCx afferents is stronger than the reverse, revealing that MSNs prioritize high-order executive processes information from the PFCx. Importantly, binge alcohol drinking alters this reciprocal inhibition by unilaterally strengthening BLA inhibition of PFCx inputs. In line with this observation, we demonstrate that in vivo optogenetic stimulation of the BLA, but not PFCx, blocks binge alcohol drinking escalation in mice. Overall, our results identify NAc MSNs as a key integrator of executive and emotional information and show that this integration is dysregulated during binge alcohol drinking.